Dramaturgia lui Fănuș Neagu – O receptare critică - Lucian Chișu (Revista de Istorie și Teorie Literară)
Best known as a prose writer – thirty books of short prose and five novels bear his signature – Fănuș Neagu was also highly appreciated as a playwright. He wrote six plays, three of which were awarded the Writers’ Union Prize – The Noise Team (1971), The Wooden Shell (1980) and The Fool Arrives on Time (1993). The critical reception of the plays written by Fănuș Neagu highlights, on the one hand, the deeply original character of the dramatic texts elaborated by the well-known author, and, on the other hand, the forms of “resistance” manifested by him against the Romanian dramatic canon and the themes/topics of the last decades of communist dictatorship. The article also deals with the theatrical seasons of the three-year period (1993 -1996) when the writer was the director of the National Theater in Bucharest.